Alelopatia de Leucena sobre soja e plantas invasoras - Mauli, Marcia Maria; Teixeira Fortes, Andrea Maria; Rosa, Danielle Medina; Piccolo, Gislaine; Marques, Denise Sommer [UNESP]; Corsato, Jaqueline Malagutti [UNESP]; Leszczynski, Raquel (Universidade Estadual de Londrina (UEL), 2009)
With the advance of agriculture, there was consequent rising in environment degradation. Therefore, It is interesting the use of plants which have in their chemical composition substances capable of helping in the control of weeds to minimize the use of pesticides. Hence, the objective of this paper was to evaluate solutions of leucena extract on weeds that are frequent on soybean crop. The treatments were leucena extracts at 0, 20, 40, 60, 80 and 100% at room temperature water and water heated to 80 degrees C. The extracts were obtained by crushing 200g of leucena leaves and mixing them with one liter of distilled water with the help of a blender. Seeds were kept in B.O.D. at a temperature of 25 degrees C, with a photoperiod of 12 hours of light. Evaluations were done oil a daily basis, from the first to the last day of the experiment, varying according to the species. Results show a negative interference of the extracts, both hot and cold, in the root length of Ipomoea grandifolia, in the percentage of germination and in the root length of Arrowleaf sida and Hair beggarticks. There was no negative interference in the analyzed parameters for soybean seeds. Thus, the results indicate allelopatic potential of Leucaena leuucocephala as an alternative for the management of weeds without interfering on the development of the soybean crop.
Leucaena allelopathy on weeds and soybean seed germination
Keywords: Allelopathy; Leucaena leucocephala; Glycine max